PENGEMBANGAN PAKET PROGRAM COACHING BERBASIS VIDEO UNTUK PENINGKATAN KOMPETENSI MENGAJAR GURU SAINS - Ari Widodo; Riandi .; Bambang Supriatno (Jurnal Cakrawala Pendidikan, 2011)
Abstract: Developing a Video-Based Coaching Program Package to Improve Science Teachers’ Teaching Competencies. A number of programs have been launched by the government to improve teachers’ teaching competencies. It seems, however, there is no significant improvement in the practice. This paper presents results of a three-year research project employing the Research and Development (R D) design. In the first year, a needs assessment was conducted to identify teachers’ needs for their professional development. Based on the results of the first year, a video-based coaching package was developed in the second year. In the final year, an experimental study was conducted to assess the effectiveness of the coaching package. The study reveals that through the coaching package there is improvement in teachers’ ability to reflect on their own practice as well as their teaching competencies. Keywords: video-based coaching, teacher competencies, teacher professionalism, science